Changes in CYP3A4 Enzyme Expression and Biochemical Markers Under Acute Hypoxia Affect the Pharmacokinetics of Sildenafil - Zhang, Juanhong; Wang, Rong (Frontiers in Physiology, 2022)
To investigate the effects of pathological, physiological, biochemical and metabolic enzymes CYP3A4 on the pharmacokinetics of sildenafil under acute hypoxia, rats were randomly divided into the plain group (50 m above sea level), acute plateau group 1 (2300 m above sea level), and acute plateau group 2 (4300 m above sea level), and blood samples and liver tissues were collected. Our results showed that the blood gas, physiological and biochemical indexes of rats changed under acute hypoxia, and the protein expression of CYP3A4 enzyme decreased. The process of absorption, distribution, metabolism and excretion of sildenafil in rats has changed. Compared with the P group, the area under the drug-time curve and the average resident in the H2 group increased to 213.32 and 72.34%, respectively. The half-life and peak concentration increased by 44.27 and 133.67%, respectively. The clearance rate and apparent distribution volume decreased to 69.13 and 46.75%, respectively. There were no statistical differences in the pharmacokinetic parameters between the P group and the H1 group. In conclusion, the pharmacokinetic changes of sildenafil have a multi-factor regulation mechanism, and changes in blood gas, pathology, and biochemical indicators and metabolic enzymes affect the absorption, distribution, excretion, and metabolism of sildenafil, respectively. This study provides experimental evidence and new ideas for the rational use of sildenafil under acute hypoxic conditions.